Legal Uncertainty Regarding the Application of The Principle of Territoriality in the Immigration Area: Ketidakpastian Hukum Penerapan Asas Teritorialitas pada Area Imigrasi - Widodo, Rizal Fitroh Dwi; Rifa’i, M. Hafiz; Wiratama, Jhonata (Rechtsidee, 2022)
The area of ​​immigration is an important aspect of immigration law enforcement and practice. This is because the immigration area preventively represents the sovereignty of a country. Even so, in the Immigration Law in Indonesia there are no special regulations regarding the immigration area. So there is the problem of a legal vacuum related to special regulations regarding the immigration area. This research is a normative legal research with a statutory and conceptual approach. The results of the study confirm that the principle of territoriality in the immigration area requires legal certainty. This is because in the practice of immigration, the principle of territoriality is an important principle, one of which is trying to prevent it from protecting the sovereignty of the state. In addition, the government needs to make a special legal product that regulates immigration areas in the form of Government Regulations and Presidential Regulations which can then be followed up technically with the regulations below. Technical follow-up to Government Regulations and Presidential Regulations can be in the form of a Regulation of the Minister of Home Affairs and specifically technical instructions regarding immigration areas can be formed for officers and law enforcement officers in the immigration sector who are specifically tasked with immigration areas.